When Can We Trust a Third Party? A Soundness Perspective - van Hee, Kees M.; Sidorova, Natalia; van der Werf, Jan Martijn E. M. (Transactions on Petri Nets and Other Models of Concurrency VIII, 2013)
Organizations often do not want to reveal the way a product is created or a service is delivered. As a consequence, if two organizations want to cooperate, they contact a trusted third party. Each specifies how it wants to communicate with the other party. The trusted third party then needs to assure that the two organizations cooperate correctly. In this paper, we study requirements on trusted third parties to ensure correct cooperation between the different organizations.